The Role of Social Media as a Campaign Tool and its Impact on the Increase of Black Campaigning in Elections and Regional Elections - Tarigan, Yos Arnold (Formosa Journal of Science and Technology, 2024)
Elections (Pemilu) are a critical mechanism in a democratic system, conducted based on the principles of direct, universal, free, secret, honest, and fair voting, as mandated by the 1945 Constitution of Indonesia. Law No. 7 of 2017 regulates electoral campaigns as activities aimed at persuading voters through the vision, mission, and image of election participants. However, in practice, Black Campaigns often occur, particularly on social media, which damage candidates' reputations through the spread of false information or defamation. This study aims to analyze the role of social media in election campaigns and its impact on the increase of Black Campaigns, which often exacerbate political polarization. The methodology used in this study is a normative legal approach, analyzing existing regulations related to election campaigns and the spread of negative content on social media. The findings indicate that although Black Campaigns are not explicitly regulated in the Election Law, they can be addressed through legal interpretation that allows for further regulation. While social media has the potential to strengthen democracy, it also serves as a platform for spreading harmful information. Therefore, stricter regulations, increased digital literacy in society, and more effective law enforcement are necessary to mitigate the negative impacts of Black Campaigns, in order to create more transparent and integrity-based elections.